Genomic characterization of Klebsiella pneumoniae clinical isolates from cancer patients: resistance profiles, virulence factors, and sequence typing - Liu, Hancong; Liu, Wan; Zhou, Xiaojuan; Wang, Xiaoli; Huang, Gang (Frontiers in Microbiology, 2025)
BackgroundKlebsiella pneumoniae (K. pneumoniae) is a major opportunistic pathogen associated with nosocomial infections, particularly in immunocompromised patients, including those with malignant cancer. The molecular epidemiology of K. pneumoniae isolated from distinct body sites from cancer patients remains poorly understood. This study aims to investigate the resistance genes, virulence factors, and sequence types of K. pneumoniae strains isolated from cancer patients to provide insights into their epidemiological and clinical characteristics.MethodsA total of 105 K. pneumoniae isolates from malignant cancer patients were subjected to whole-genome sequencing. Resistance genes, virulence- associated genes, and multilocus sequence typing (MLST) were analyzed. The distribution of these genetic determinants was compared among isolates from distinct body sites from cancer patients. Whole-genome sequencing was performed on 105 K. pneumoniae isolates obtained from the blood and body fluids of patients with various cancers, including lung (n = 24), nasopharyngeal (n = 12), liver (n = 11), cervical (n = 8), and other cancer types (n = 50). The isolates were characterized in terms of antimicrobial resistance genes, virulence-associated genes, and MLST. Additionally, virulence was evaluated using a scoring system incorporating the virulence genes ybt, clb, and iuc.ResultsAmong the isolates, 41 exhibited resistance to trimethoprim-sulfamethoxazole, predominantly harboring sul1, sul2, and dfrA genes. Resistance to tobramycin and levofloxacin was mainly associated with aadA16, aph(3″)-Ib, and AAC(6′)-Ib-cr genes. Eight isolates were identified as carbapenem-resistant K. pneumoniae (CRKP), carrying resistance genes bla_kpc-1, bla_ndm-5, and bla_oxa-10. Virulence genes included iron siderophores (entAB, ybt, iucABC), fimbriae (fimA, fimH), and OmpA (100%). Notably, isolates from cervical cancer patient samples had the lowest virulence scores, whereas those from lung and nasopharyngeal cancer patient samples demonstrated the highest virulence scores. MLST revealed 45 sequence types, with ST23 predominating in isolates from lung and nasopharyngeal cancer patient, while ST45 was the most frequent in cervical cancer patient isolates. Phylogenetic analysis demonstrated clustering of Klebsiella pneumoniae isolates from lung, nasopharyngeal, liver, and cervical cancer patient samples, with these isolates predominantly located within the third clade, accounting for 58.3, 66.7, 80, and 87.5%, respectively.ConclusionThe K. pneumoniae isolates in this study demonstrate considerable diversity in their virulence genes, antimicrobial resistance genes, and sequence types. The findings highlight the importance of genomic surveillance to guide infection control and therapeutic strategies, particularly in high-risk oncology settings.